Trabalho doméstico: entre o poder simbólico patronal e a luta por reconhecimento jurídico - Attila Magno e Silva Barbosa; Giovanna Iasiniewicz; Maria Emília Valli Büttow (Ciências Sociais Unisinos)
This article aims to analyse how social agents perceive social relations between employers and domestic workers after the establishment of the Constitutional Amendment No. 72, 2013, and the Complementary Law No. 150/15, giving an special focus to issues of power relations, affects and professionalization of such employment relationship. The fight for legal recognition and the expansion of labour rights are to combat situations of inequality, vulnerability and devaluation of domestic work. However, it is necessary to question whether the transformation in the working relationship between these agents can promote an effective rupture with the paternalistic and ‘clientelistic’ social arrangement that has traditionally characterised this type of work. Among the methodological procedures used to obtain the data, includes eighteen semi-structured interviews and direct observation conducted at the headquarters of the Domestic Workers’ Union of Pelotas - seeking to understand the perception of domestic workers, employers and trade unionists about the recent changes.